Acoustic characterization of Abaca Wool as a natural sound absorber: experimental and simulation approach - Mafaz, Bilqia; Zainuri, Mochamad (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
The increasing environmental and health concerns associated with synthetic sound-absorbing materials such as rockwool and fiberglass—due to their non-biodegradable nature and potential respiratory hazards—have prompted the exploration of sustainable alternatives. This study introduces Abaca-wool, a bio-based acoustic material derived from abaca banana fibers (Musa textilis) engineered to mimic the structure of mineral wool. The research aimed to evaluate the acoustic performance of Abaca-wool through both experimental measurements and numerical simulations, while examining the influence of fiber morphology on sound absorption. The fabrication process involved alkaline treatment with 15% NaOH, followed by sequential wet and dry refining to produce a randomly entangled, porous structure. Microscopic analysis revealed micro-diameter fibers and high porosity (~93%), which are critical for enhancing viscoelastic interactions between air particles and fiber walls. Key physical parameters—density and airflow resistivity (64.117 kPa·s/m²)—were measured to support numerical modeling using AFMG SoundFlow. Experimental results using the two-microphone impedance tube method showed high absorption coefficients, peaking at 0.89 at high frequencies and 0.83 at around 1000 Hz. The observed performance is attributed to optimized fiber morphology, which facilitates energy dissipation through friction and acoustic scattering. Numerical simulations exhibited good agreement with experimental data, with minor deviations linked to the homogeneous assumptions in the model. Overall, Abaca-wool demonstrates excellent potential as a biodegradable, low-density, and high-performance acoustic material, offering a viable and environmentally responsible alternative to conventional synthetic absorbers.